Postoperative pediatric cerebellar mutism syndrome: A literature review - Matheus Ballestero; Rodrigo Inácio Pongeluppi; Ricardo Santos de Oliveira (Brazilian Society for Pediatric Neurosurgery, 2023)
Introduction: Postoperative pediatric cerebellar mutism syndrome (POPCMS) is a significant complication observed after posterior fossa surgery for tumors, particularly in pediatric neurosurgery. This paper presents a literature review on the physiopathology, diagnosis, treatment, and long-term outcomes of POPCMS. Methods: A systematic review following PRISMA guidelines, searching for articles published in PubMed, Web of Science, and Lilacs in the last ten years. Inclusion criteria involved studies on human subjects under 18 years of age, focusing on the pathophysiology, diagnosis, treatment, and outcome of POPCMS. Results: The review identified 34 studies on POPCMS for final inclusion. Preoperative risk factors commonly associated with cerebellar mutism included midline tumor location, diagnosis of medulloblastoma, younger age at diagnosis, preoperative language impairment, brainstem infiltration, and tumor histology. The SHH subgroup was found to reduce the risk of CMS. Diagnostic criteria for POPCMS included language impairment, emotional lability, hypotonia, oropharyngeal dysfunction, dysphagia, cerebellar motor syndrome, cerebellar cognitive affective syndrome, and brainstem dysfunction. Treatment approaches varied, with medications showing potential benefits. Rehabilitation options for speech and language deficits were limited. Cognitive remediation programs showed promise in improving academic achievement and attention. A significant proportion of patients experienced clinical improvement.  Conclusion:  POPCMS remains a challenging complication following posterior fossa surgery. Further research is needed to develop standardized diagnostic criteria, effective treatments, and rehabilitation strategies to improve long-term outcomes for patients with POPCMS.